PELATIHAN SANITASI TOTAL BERBASIS MASYARAKAT (STBM) STUNTING DI KALURAHAN ARGODADI KAPANEWON SEDAYU KABUPATEN BANTUL YOGYAKARTA - Sigid Sudaryanto; Naris Dyah Prasetyawati; Hanung Prasetya; Tri Siswati; Agus Sarwo Prayogi; Anita Rahmawati (Bajang Institute, 2021)
Community-Based Total Sanitation is an approach and paradigm of sanitation development in Indonesia that emphasizes maximizing community empowerment through triggering to increase behavior change, especially behavior change in terms of sanitation. In addition to nutritional conditions, poor environmental factors related to drinking water and sanitation can also increase the risk of stunting. There is a very close relationship between poverty, access to drinking water, and sanitation and the incidence of stunting. One of the efforts to integrate the acceleration of nutrition improvement through stunting prevention, since 2017 various pieces of training involving nutrition and environmental health officers have begun to be provided. The addition of an output indicator of 3 stunting pillars so that currently there are 8 STBM-Stunting pillars. The material was delivered using the principles of adult learning, followed by simulation and practice of triggering the STBM pillar. Participants were health cadres and the stunting prevention team of Argodadi Village. Through practical simulations in training, then health cadres are expected to be able to trigger STBM-stunting. In the final session as a follow-up plan, the cadres agreed on a commitment to conduct similar training in their respective hamlet areas